Patient Prioritization Preferences among Physiotherapy Entry-Level Students: The Importance of Chronic Pain - Laliberté, Maude (University of Toronto Press Incorporated, 2013)
Purpose: To investigate physiotherapy entry-level students' preferences in prioritizing patients, specifically, patients with chronic pain. Methods: After a group discussion, 249 Canadian entry-level physiotherapy students completed a questionnaire that used five distinct scenarios (fictitious patient cases). Respondents were asked to prioritize the patients (P1=highest priority, P5=lowest priority). Results: Physiotherapy students accorded the highest priority to the patient with chronic pain and the post-surgical patients; the elderly patient and the patient with cognitive impairment were given low priority. Conclusions: A diagnosis of chronic pain is given the highest level of priority by physiotherapy students. The literature shows, however, that chronic pain is given the lowest priority in physiotherapy department triage tools. There may be a shift in preferences with respect to patients with chronic pain between the pre-licensure (student) phase and the post-licensure (clinician) phase.